Impact of Dietary Protein Content on Soil Bacterial and Fungal Communities in a Rice–Crab Co-culture System - Li, Yingdong; Li, Lisong; Yu, Yilin; Hu, Qingbiao; Li, Xiaodong (Frontiers in Microbiology, 2021)
Although co-culture of paddy fields with aquatic animals is lucrative, the ecological impacts of high-protein content entering the agricultural soil via animal pellet feed and feces have not been well studied. Moreover, the effects of dietary protein on soils and soil microbes remain unclear. To elucidate this, we examined soil bacterial and fungal community composition and temporal changes in paddy fields subjected to different protein-content diets via 16S/18S rRNA gene amplicon sequencing analysis with a high-throughput next-generation sequencer. MiSeq sequencing revealed that protein content significantly impacted fungal community structure. High-protein diets reduced bacterial community diversity and relative abundance in both July and October. The phylum-level bacterial taxonomic composition was not affected by diet treatment, while in fungi, a major phylum-level shift was evident. Hierarchically clustered analysis showed that high-protein diets significantly reduced the relative abundance of Brevundimonas in both July and October. Saprotrophic macrofungal diversity was negatively related to dietary protein content. Considering microbial community structure and environmental factors, ca. 15% protein content is appropriate for the rice-crab co-culture system that we studied.